VMAT for the treatment of gynecologic malignancies for patients unable to receive HDR brachytherapy. (8th September 2014) - Merrow, Caitlin; deBoer, Steven; Podgorsak, Matthew B.
Abstract : This investigation studies the use of volumetric‐modulated arc therapy (VMAT) to deliver the following conceptual gynecological brachytherapy (BT) dose distributions: Type 1, traditional pear‐shaped dose distribution with substantial dose gradients; Type 2, homogeneous dose distribution throughout PTV (BT prescription volume); and Type 3, increased dose to PTV without organ‐at‐risk (OAR) overdose. A tandem and ovoid BT treatment plan, with the prescription dose of 6 Gy to point A, was exported into the VMAT treatment planning system (TPS) and became the baseline for comparative analysis. The 200%, 150%, 130%, 100%, 75%, and 50% dose volumes were converted into structures for optimization and evaluation purposes. The 100% dose volume was chosen to be the PTV. Five VMAT plans (Type 1) were created to duplicate the Ir‐192 tandem and ovoid inhomogeneous dose distribution. Another five VMAT plans (Type 2) were generated to deliver a homogeneous dose of 6 Gy to the PTV. An additional five VMAT plans (Type 3) were created to increase the dose to the PTV with a homogeneous dose distribution. In the first set of plans, the dose given to 99% of the 200%–100% dose volumes agreed within 2% of the BT plan on average. Additionally, it was found that the 75% dose volumes agreed within 5% of the BT plan and the 50% dose volumes agreed within 6.4% of the BT plan. In the second set of comparative analyses, the 100% dose volume was found to be within 1% of the original plan. Furthermore, the maximum increase of dose to the PTV in the last set of comparative analyses was 8 Gy with similar doses to OARs as the other VMAT plans. The maximum increase of dose was 2.50 Gy to the rectum and the maximum decrease of dose was 0.70 Gy to the bladder. Henceforth, VMAT was successful at reproducing brachytherapy dose distributions demonstrating that alternative dose distributions have the potential to be used in lieu of brachytherapy. It should also be noted that differences in radiobiology need to be further investigated. PACS numbers: 87.50.‐a, 87.53.‐j, 87.55.‐x, 87.55.D‐, 87.55.dk, 87.55.de